Noise in and as music - Cassidy, Aaron; Einbond, Aaron (University of Huddersfield Press, 2013)
One hundred years after Luigi Russolo's "The Art of Noises," this book exposes a cross-section of the current motivations, activities, thoughts, and reflections of composers, performers, and artists who work with noise in all of its many forms. The book's focus is the practice of noise and its relationship to music, and in particular the role of noise as musical material-as form, as sound, as notation or interface, as a medium for listening, as provocation, as data. Its contributors are first and foremost practitioners, which inevitably turns attention toward how and why noise is made and its potential role in listening and perceiving. Contributors include Peter Ablinger, Sebastian Berweck, Aaron Cassidy, Marko Ciciliani, Nick Collins, Aaron Einbond, Matthias Haenisch, Alec Hall, Martin Iddon, Bryan Jacobs, Phil Julian, Michael Maierhof, Joan Arnau Pàmies, and James Whitehead (JLIAT). The book also features a collection of short responses to a two-question "interview"-"what is noise (music) to you?" and "why do you make it?"-by some of the leading musicians working with noise today. Their work spans a wide range of artistic practice, including instrumental, vocal, and electronic music; improvisation; notated composition; theater; sound installation; DIY; and software development. Interview subjects include Eryck Abecassis, Franck Bedrossian, Antoine Chessex, Ryan Jordan, Alice Kemp (Germseed), George Lewis, Lasse Marhaug, Maja Solveig Kjelstrup Ratkje, Diemo Schwarz, Ben Thigpen, Kasper Toeplitz, and Pierre Alexandre Tremblay.